Theory of Law understood as Prudential Theory of Law - Puy Muñoz, Francisco (2017)
During centuries, law has been studied and understood under a human view. This way of understanding law used the argumentation, the topic, the rhetoric and the dialectics as working methods. The result was a plural and continuously in movement humanistic law. The situation changes in 19 century with the beginning of the iuspositivism movements with a focus in the study of law as legal frame. The result is a rigid, non-flexible and poorly adapted to judicial experience law. We understand that this situation must change and is urgent to combine science and prudence in order to be able to provide a Theory of law, that can be understood as a Prudential Theory of Law. This according to our understanding will enable the recuperation of a more flexible, plural and humanistic and above anything a fairer judicial experience.